Korsakoff Syndrome in Non-alcoholic Psychiatric Patients. Variable Cognitive Presentation and Impaired Frontotemporal Connectivity - Nikolakaros, Georgios; Kurki, Timo; Paju, Janina; Papageorgiou, Sokratis G.; Vataja, Risto; Ilonen, Tuula (Frontiers in Psychiatry, 2018)
Background: Non-alcoholic Wernicke's encephalopathy and Korsakoff syndrome are greatly underdiagnosed. There are very few reported cases of neuropsychologically documented non-alcoholic Korsakoff syndrome, and diffusion tensor imaging (DTI) data are scarce. Methods: We report clinical characteristics and neuropsychological as well as radiological findings from three psychiatric patients (one woman and two men) with a history of probable undiagnosed non-alcoholic Wernicke's encephalopathy and subsequent chronic memory problems. Results: All patients had abnormal neuropsychological test results, predominantly in memory. Thus, the neuropsychological findings were compatible with Korsakoff syndrome. However, the neuropsychological findings were not uniform. The impairment of delayed verbal memory of the first patient was evident only when the results of the memory tests were compared to her general cognitive level. In addition, the logical memory test and the verbal working memory test were abnormal, but the word list memory test was normal. The second patient had impaired attention and psychomotor speed in addition to impaired memory. In the third patient, the word list memory test was abnormal, but the logical memory test was normal. All patients had intrusions in the neuropsychological examination. Executive functions were preserved, except for planning and foresight, which were impaired in two patients. Conventional MRI examination was normal. DTI showed reduced fractional anisotropy values in the uncinate fasciculus in two patients, and in the corpus callosum and in the subgenual cingulum in one patient. Conclusions: Non-alcoholic Korsakoff syndrome can have diverse neuropsychological findings. This may partly explain its marked underdiagnosis. Therefore, a strong index of suspicion is needed. The presence of intrusions in the neuropsychological examination supports the diagnosis. Damage in frontotemporal white matter tracts, particularly in the uncinate fasciculus, may be a feature of non-alcoholic Korsakoff syndrome in psychiatric patients.